IMPLEMENTASI PELATIHAN MAKE’UP SEBAGAI BENTUK PEMBERDAYAAN DALAM PENGEMBANGAN KETERAMPILAN WARGA BINAAN PEREMPUAN DI LAPAS KELAS III RANGKASBITUNG - Giyanah, Siti; Ahmad Fauzi; Yosi Asri Badrio (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of make-up training as a form of empowerment in developing the skills of female inmates at Class III Rangkasbitung Correctional Institution. The study was motivated by the importance of skill-based development programs as an effort to improve the abilities, self-confidence, and readiness of inmates in facing life after release. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of six female inmates who participated in the make-up training program. Data were collected through observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing using source and technique triangulation to ensure data validity. The results showed that the make-up training improved participants’ skills in basic facial make-up techniques through direct practice methods. In addition, the training had a positive impact on increasing participants’ self-confidence, courage, and motivation. The program also broadened participants’ perspectives regarding opportunities for economic independence through make-up skills that could be utilized as a source of income after release. However, the implementation of the training still faced several obstacles, including limited equipment, materials, and training time. Therefore, make-up training can be considered an effective form of empowerment in supporting the rehabilitation and social reintegration process of female inmates in correctional institutions.